Biotic and abiotic predictors of potential N2O emissions from denitrification in Irish grasslands soils: A national-scale field study. (May 2022) - Deveautour, C.; Rojas-Pinzon, P.A.; Veloso, M.; Rambaud, J.; Duff, A.M.; Wall, D.; Carolan, R.; Philippot, L.; Richards, K.G.; O'Flaherty, V.; Brennan, F.
Abstract: Large-scale information regarding nitrous oxide (N2 O) emissions is needed as an evidence base to underpin land use policy and mitigation approaches. However, the highly variable rates of denitrification make the prediction of N2 O emission demanding. Here, we evaluated the role of abiotic and biotic factors on the potential denitrification of Irish soils, in order to identify the key factors regulating potential N2 O emissions at a large scale. To do so, we collected 136 soil samples from 32 sites across Ireland, and characterised the soil physico-chemical properties, the prokaryotic and fungal community composition, the abundance of N-cycling genes and evaluated the soil potential nitrification, denitrification and end product N2 O/(N2 O + N2 ). We found large differences in soil potential denitrification between sites (up to 41.5 mg N2 O–N kg −1 soil day −1 ) with most of the emissions released in the form of N2 O rather than N2 . Soils with highest potential nitrification rates also exhibited the highest potential denitrification rates, and similar parameters were linked to both processes. The factors most predictive of soil potential denitrification were soil physico-chemical properties and the prokaryotic community composition. Soil phosphorus content was as important for predicting potential denitrification as was pH and total nitrogen. Soil microbial community structure, rather than denitrifier abundance, was an important predictor of the potential denitrification and the end-product N2 O/(N2 O + N2 ). The prokaryotic community composition was more strongly associated with denitrification rates and the resulting end-products than fungal communities. Increased relative abundance of the prokaryotic phyla Actinobacteriota and Crenarchaeota, were positively correlated to complete denitrification. Altogether, these results lay the foundation for a better understanding of the key factors regulating the potential denitrification in soils and identify important properties that enhance prediction of the potential denitrification at larger scales. Highlights: Soils with highest nitrification also had the highest denitrification potential (PD). Soil phosphorus was as important predicting PD as was pH and total nitrogen. The prokaryotic community was more predictive of soil PD than the fungal community. Microbial community structure, rather than gene abundance, was an important predictor. Actinobacteriota and Crenarchaeota were correlated to complete denitrification.